2019
DOI: 10.1039/c9cc01276a
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic protein hydrogels with reversibly tunable stiffness regulate human lung fibroblast spreading reversibly

Abstract: Fibroblast cells change their morphology reversibly in response to changes in protein hydrogel stiffness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 34 publications
0
44
0
Order By: Relevance
“…For example, one study has shown that hepatic stellate cells cultured on active MeHA hydrogel substrates respond to dynamic changes in matrix stiffness (20-fold) by spreading, changing actin fiber organization to form stress fibers of α-smooth muscle actin (α-SMA), and increasing nuclear YAP content, all indicative of myofibroblast differentiation [43]. Similar observations have been made using other active biomaterials [36], [59], [66], [77], [78], [135]. In contrast, matrix softening was reported to induce valvular myofibroblast de-activation [31].…”
Section: Manipulation Of Mechanotransduction Associated With Cell-endogenous Forcesmentioning
confidence: 64%
See 1 more Smart Citation
“…For example, one study has shown that hepatic stellate cells cultured on active MeHA hydrogel substrates respond to dynamic changes in matrix stiffness (20-fold) by spreading, changing actin fiber organization to form stress fibers of α-smooth muscle actin (α-SMA), and increasing nuclear YAP content, all indicative of myofibroblast differentiation [43]. Similar observations have been made using other active biomaterials [36], [59], [66], [77], [78], [135]. In contrast, matrix softening was reported to induce valvular myofibroblast de-activation [31].…”
Section: Manipulation Of Mechanotransduction Associated With Cell-endogenous Forcesmentioning
confidence: 64%
“…Similarly, a four-fold increase of stiffness was observed in DNA crosslinked polyacrylamide substrates [77]. Reversible stiffening over several cycles was demonstrated in dynamic protein hydrogels that undergo secondary crosslinking between tyrosine residues due to redox reactions [78], or tyrosinase enzyme [79], [80]. In contrast, sortase enzyme mediated crosslinking led to reversible stiffening in PEG-peptide hydrogels [81].…”
Section: Chemical Control Of Matrix Structurementioning
confidence: 92%
“…Adapted with permission. [ 72 ] Copyright 2019, Royal Society of Chemistry. D) Self‐healing protein hydrogels constructed by crosslinking SAE proteins with mechanically stable noncovalent ligand–receptor interactions.…”
Section: Protein Mechanics Has Made It Possible To Engineer Protein‐based Biomaterials To Mimic the Passive Elastic Properties Of Musclesmentioning
confidence: 99%
“…Using a redox‐controlled mutually exclusive protein, which behaves as a redox‐controlled protein folding switch, we engineered dynamic protein hydrogels that can change their Young's modulus in response to redox potential. [ 58,72,73 ] The Young's modulus of the hydrogel can be switched between a lower and a higher value, which differ by 2–4 times, by redox potential in a fully reversible fashion (Figure 4C). Liu et al used a Ca 2+ ‐responsive RTX protein, which folds into a Ca 2+ ‐loaded β‐roll structure in the presence of Ca 2+ and behaves as a random coil in the absence of Ca 2+ , to construct Ca 2+ ‐responsive protein hydrogels.…”
Section: A Diverse Range Of Sae Proteins For Constructing Protein Hydrogels: Imparting Novel Properties To Protein Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation